Assessing the Influence of Mega Sporting Events on the Entrepreneurial Ecosystems of Host Nations - Mammadov, Rauf (IE University, 2026)
This thesis investigates the multifaceted influence of mega sporting events (MSEs) on entrepreneurial ecosystems (EEs) in host countries, a topic of growing scholarly interest at the intersection of entrepreneurship and sports event management. It evaluates four hypotheses: (H1) that MSEs positively impact EEs; (H2) that this impact is stronger for more popular; (H3) that the impact is greater in economically developed countries; and (H4) that the effect is more pronounced in countries with higher rule of law. To test these hypotheses, the study employs a dynamic difference-in-differences (DID) regression model covering multiple sport events and host countries from 2009 to 2018. Coarsened Exact Matching (CEM) is applied to pre-process the dataset, ensuring balanced comparison groups and enhancing the robustness of causal inference. This method enhances the validity of the DID model by allowing for a more precise estimation of the causal effects of MSEs. Findings indicate that hosting MSEs is associated with improvements in the quality of EEs in host nations. Furthermore, the study also demonstrates that the associations are stronger for more popular events, more economically developed countries, and those with higher rule of law. This thesis provides empirical evidence supporting the positive effects of MSEs, offering insights for policymakers and event organisers to strategically leverage these events. The research reveals a dynamic relationship between MSEs and EEs, enriching theoretical discourse and providing practical implications for fostering sustainable entrepreneurial ecosystems in the context of large-scale sporting events.

Esta tesis investiga la influencia multifacética de los megaeventos deportivos (MSE por sus siglas en inglés) en los ecosistemas emprendedores (EE por sus siglas en inglés) de los países anfitriones, un tema de creciente interés académico en la intersección entre el emprendimiento y la gestión de eventos deportivos. Evalúa cuatro hipótesis: (H1) que los MSE ejercen un impacto positivo en los EE; (H2) que este impacto es más fuerte cuanto más populares son; (H3) que el impacto es mayor en los países económicamente desarrollados; y (H4) que el efecto es más pronunciado en los países con un estado de derecho más sólido. Al objeto de comprobar estas hipótesis, el estudio emplea un modelo de regresión dinámica de diferencias en diferencias (DID por sus siglas en inglés) que abarca múltiples eventos deportivos y países anfitriones desde 2009 hasta 2018. Se aplica el emparejamiento exacto aproximado (CEM por sus siglas en inglés) para preprocesar el conjunto de datos, lo que garantiza la comparabilidad entre grupos y fortalece la validez de la inferencia causal. Este método refuerza la validez del modelo DID al permitir una estimación más precisa de los efectos causales de los MSE. Los resultados indican que la celebración de MSE se asocia con mejoras en la calidad de los EE en los países anfitriones. Adicionalmente, el estudio demuestra que dichas asociaciones son más fuertes en el caso de los eventos más populares, los países con mayor desarrollo económico y aquellos con un estado de derecho más sólido. Esta tesis proporciona pruebas empíricas que respaldan los efectos positivos de los MSE y ofrece información útil para que los responsables de las políticas públicas y los organizadores los aprovechen estratégicamente. La investigación revela una relación dinámica entre los MSE y los EE que enriquece el debate teórico y hace aportaciones prácticas para fomentar ecosistemas emprendedores sostenibles en el contexto de eventos deportivos de gran escala.
Evaluación de la Influencia de los Megaeventos Deportivos en los Ecosistemas Emprendedores de los Países Anfitriones
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 8 - Trabajo decente y crecimiento económico; Mega Sporting Event; Entrepreneurial Ecosystem; Impact Assessment; Legacy; Policy Implications